Telemedicine for the management of diabetic patients in a high-complexity Latin American hospital - Luz Angela Casas; Juliana Alarcón; Alejandra Urbano; Evelyn E. Peña-Zárate; Saveria Sangiovanni; Laura Libreros-Peña; María Fernanda Escobar (BMC, 2023)
Abstract Background Noncommunicable diseases such as diabetes mellitus (DM) have gained attention worldwide. Latin America experienced a rise in rates of DM. During the COVID-19 pandemic, a telemedicine program was implemented in a quaternary care academic complex in Latin America to continue the follow-up of patients with diabetes. Objective The aim of this study is to describe the clinical experience of DM patient management through telemedicine and the HbA1c behavior of patients followed-up through this modality. Materials and methods We conducted a retrospective cohort study including all patients with type 1 or 2 diabetes who were treated via telemedicine from March to December 2020. A Wilcoxon statistical test was used to compare the changes in glycosylated hemoglobin between the first teleconsultation and after 6 months of telemedicine follow-up. Results A total of 663 patients were included, 17.65% (117) of whom had type 1 diabetes and 82.35% (546) of whom had type 2 diabetes. Patients with both types of diabetes, presented with stable HbA1c values regardless of the length of follow-up. Conclusion The use of telemedicine can be a helpful tool for both patients and health care providers to support the continuity of care to maintain acceptable control levels within glycemic control goals.